Jewish existence in Indonesia: identity, recognition, and prejudice - Rachman, Adelia Hanny (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2022)
The Jews’ arrival to the archipelago began acquainted in the 13th to the 20th century, although, much earlier, history shows the Jew’s traffic in the Southeast Asian region had eventuated. In this study, Jew accommodates several meanings, religion – Judaism and the adherents – Jewish or Jewish descendants. Practically, the beliefs’ differences are arduously accepted by a few Indonesians. Various stereotypes are imposed on this community as a form of othering. Moreover, radical ideological propaganda encompassing antisemitism incitement is presented conditionally. The absence of legal acknowledgement has impacted limiting Jews’ precious wiggle room in enforcing their religious freedom. As a further consequence, they will prefer to conceal their identity to hinder friction or disputes with the opposition. Misleading perceptions about Jews and Israel implicitly politicized identities. Aware of the rising negative sentiments, this paper provides an overview of the Jewish existence in Indonesia, from the historical journey, recognition, and prejudice to identity politics. Analysis of legislation and actual reality is carried out to find out the urgency of recognizing Jews’ identity. In the end, Indonesia endures the essential duty to fulfil religious freedom and nurture its diversity for peace.